School and Family Environment as Predictors of Students’ Learning Interest in Rural Elementary Education - Apriyanti Apriyanti; Bukman Lian; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines the influence of school environment and family environment on students’ learning interest in a rural elementary school setting, where external motivational supports are often limited. A quantitative correlational design was employed at SD Negeri 01 Adu Manis, Semendawai Barat District, Ogan Komering Ulu Timur Regency, South Sumatra. The population comprised 97 students, with a sample of 47 students from grades III, IV, and V selected through proportional sampling. Data were collected using questionnaires, observation, and documentation. Instruments measured school environment, family environment, and learning interest, with data analyzed using simple and multiple linear regression via SPSS. Results – The school environment demonstrated a positive and significant influence on learning interest (R² = 0.986), as did the family environment (R² = 0.833). Simultaneously, both variables collectively explained 99.2% of the variance in learning interest (R² = 0.992), indicating an exceptionally strong predictive capacity. This study provides empirical evidence from an underexplored rural Indonesian context, demonstrating the near-total combined explanatory power of school and family environments on student engagement. Findings underscore the critical need for structured school-family partnership programs to sustain and enhance learning interest, particularly in geographically isolated areas. This research contributes actionable insights for educators and policymakers, affirming that synergistic investments in both school climate and parental involvement are indispensable for fostering student motivation and academic persistence in rural elementary education.